2010
DOI: 10.1007/s11630-010-0014-8
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of a high-subsonic axial-flow compressor rotor with non-axisymmetric hub endwall

Abstract: The major source of loss in modern compressors is the secondary loss. Non-axisymmetric endwall profile contouring is now a well established design methodology in axial flow turbines. However, flow development in axial compressors is differ from turbines, the effects of non-axisymmetric endwall to axial compressors requires flow analysis in detail. This paper presents both experimental and numerical data to deal with the application of a non-axisymmetric hub endwall in a high-subsonic axial-flow compressor. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Hu et al. 24 exerted NAEP on hub of a compressor rotor and it could mitigate secondary flow. Iliopoulou et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hu et al. 24 exerted NAEP on hub of a compressor rotor and it could mitigate secondary flow. Iliopoulou et al.…”
Section: Introductionmentioning
confidence: 99%
“…Chu et al 23 designed a NAEP based on endwall velocity modification method, which reduced the endwall loss in an axial compressor. Hu et al 24 exerted NAEP on hub of a compressor rotor and it could mitigate secondary flow. Iliopoulou et al 25 optimized the profiled hub endwall of a compressor rotor, which showed that the performance improvement was due to the influence of shock rather than the variation of secondary flows.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with active flow control methods, passive flow control methods can be achieved easily by device with the relatively simple geometry and does not require any external energy supply. Many passive flow methods have been investigated in axial compressors, including three-dimensional blade shaping, 10 endwall profiling, 11,12 and vortex generators. 13 These passive flow control methods can restrain corner separations and display the huge potential to improve the aerodynamic performance of highly loaded axial compressors.…”
Section: Introductionmentioning
confidence: 99%
“…The other method is based on previous experience, which is well developed in turbines but seldom published in compressors except for Hu's paper. 3 The perturbation of the end wall geometry in this approach is defined using some smooth function, which is commonly controlled by very few parameters. The values of parameters are typically given by previous experience and adjusted by trial-and-error to find a satisfactory result.…”
Section: Introductionmentioning
confidence: 99%
“…An optimization procedure is then performed via a certain algorithm to get the optimum result. The other method is based on previous experience, which is well developed in turbines but seldom published in compressors except for Hu's paper [3] . The perturbation of the end wall geometry in this approach is defined using some smooth function, which is commonly controlled by very few parameters.…”
mentioning
confidence: 99%